What happens when we ask? A phenomenological focus group on HIV prevention and sexual health education among emancipated foster care youth. (September 2022) - Opara, Ijeoma; Lizarraga, Ashley; Lardier, David T.; Herrera, Andriana; Garcia-Reid, Pauline; Reid, Robert J.
Highlights: Foster care youth are more likely to have worse sexual health outcomes including diagnoses of HIV than youth not in foster care. Youth in the study felt there is a strong need for a comprehensive sexual health education programming for their group. Engaging foster care youth in empowering activities can be an effective HIV prevention strategy for this group. Youth in the study developed an arts-based HIV awareness campaign in their community after participating in focus groups. Abstract: Youth of color who have recently been emancipated from foster care are among the most vulnerable group at risk for having poor sexual health outcomes. It is essential for researchers to understand how emancipated foster care youth receive messages about safe sex and HIV/STI prevention in order to tailor health promotion activities for this group. This study presents a strengths-based view of emancipated foster care youth of color who developed an empowering, arts-based campaign to prevent HIV in their community using Youth Participatory Action Research (Y-PAR) methods. The project was led by 10 emancipated foster care youth who participated in two focus groups that centered on understanding their knowledge of HIV. Five major themes emerged from the focus group. Implications for researchers include incorporating safe spaces for youth to develop ideas that can result in empowering activities relating to prevention.